Performance of Free-Piston Linear Generator by Using Com-pressed Air - Jamal, Amir Z.; Ramlan, N. Amalina; A, Ezrann Z. Zainal; Aziz, A. Rashid A.; ah, Firmansy (International Journal of Engineering and Technology, 2018)
Free-piston linear generator (FPLG) engine combines a linear engine coupled to a permanent-magnet assembly. High Pressure UTP FPLG engine was invented as a new source of green power generation. The working principle of expansion of compressed air in a two-stroke dual piston engine was used to convert kinetic energy into electrical energy via electromagnetic induction. Electric power generated directly from the moving piston-rod-magnet assembly forced by the expansion of compressed air. Excess electricity from renewable energy sources can be converted into energy stored as compressed air. The expansion process of compressed air in the power stroke is examined by varying the parameters such as air injection supply pressure, valve injection timing and air flowrate. It was observed through expeimentally higher supply pressure gives higher power generation but results in lower efficiency.